Uderstanding user experience of an open design-clothing product - Uliana Perez, Lana (2022)
Few studies related open design to the clothing sector, but none explored how users would ex-perience it. The study reported here aimed to investigate how people with some or without prior sewing knowledge - advanced and ama-teur users – experience an open design-clothing product. Following four fashion design heuristics, a garment was created and distributed as DIY kits among advanced and amateur users. Data were collected in two stages: assembly and per-sonalization. The results indicate that although skills play a significant role during assembly, other factors, like cross-generational differences and personal taste, influence how users experi-ence an open design product. Furthermore, the study shows that given the necessary support, the open design can be used by a heteroge-neous public, amplifying the participation of users with little or without prior sewing skills in clothing co-creation.